Role of the Inflammatory Response of RAW 264.7 Cells in the Metastasis of Novel Cancer Stem-Like Cells - Chan-Yen Kuo; Tzu-Hsien Yang; Pei-Fang Tsai; Chun-Hsien Yu (Medicina, 2021)
Background and objectives: Tumor progression and the immune response are intricately linked. Additionally, the presence of macrophages in the microenvironment is essential for carcinogenesis, but regulation of the polarization of M1- and M2-like macrophages and their role in metastasis remain unclear. Based on previous studies, both reactive oxygen species (ROS) and the endoplasmic reticulum (ER) are emerging as key players in macrophage polarization. While it is known that cancers alter macrophage inflammatory responses to promote tumor progression, there is limited knowledge regarding how they affect the macrophage-dependent innate host defense. Materials and methods: We detected the levels of ROS, the ability of chemotaxis, the expressions of markers of M1-/M2-like macrophages in RAW264.7 in presence of T2- and T2C-conditioned medium. Results: The results of this study indicated that ROS levels were decreased in RAW 264.7 cells when cultured with T2C-conditioned medium, while there was an improvement in chemotaxis abilities. We also found that the M2-like macrophages were characterized by an elongated shape in RAW 264.7 cells cultured in T2C-conditioned medium, which had increased CD206 expression but decreased expression of CD86 and inducible nitric oxide synthase. Suppression of ER stress shifted polarized M1-like macrophages toward an M2-like phenotype in RAW 264.7 cells cultured in T2C-conditioned medium. Conclusions: Taken together, we conclude that the polarization of macrophages is associated with the alteration of cell shape, ROS accumulation, and ER stress.